Watershed politics and climate change in Peru - Stensrud, Astrid B. (Anthropology, culture, and society., 2021)
This book travels to the heart of power, inequality and injustice in water politics. Drawing on extensive ethnographic fieldwork in Peru, Astrid B. Stensrud explores the impact of Integrated Water Resources Management (IWRM), an extractivist global water paradigm that views water as a finite resource in need of management. Where the local bureaucracy has adapted to IWRM and a new water culture is being fostered amongst the population, Stensrud examines the tensions arising between 'indigeneity' and 'modernity', between cultural practices and questions of power. Engaging with the many different actors and entities participating in the constitution of the watershed - from engineers, politicians and bureaucrats, to farmers, workers and animals - Stensrud shines light on how both the watershed and our understanding of water itself have changed over the last few decades. Methodologically innovative, Watershed Politics and Climate Change in Peru makes an original contribution to the scholarship on global-local relationships.